The Study of Syntactic Error Review of Editorial News Titled Politics is Getting Hotter - Erwan Efendi*; Azzahra Putri Hermaya; Lisa Ferina; Surya Surya (Universitas Syiah Kuala, 2023)
The background of this research is the discovery of errors in the Indonesian language in online news writing. The most obvious error is at the syntax level. Therefore, this study aims to explain the form of language errors in the field of syntax contained in the online news portal Sindonews in the editorial news text entitled